Extraordinary chambers in the courts of Cambodia (ECCC) 16 November 2018 - Klip, André 1965-; Freeland, Steven 1957-; Häberle, Victoria; Deák, Enikő (Annotated leading cases of international criminal tribunals, 2022)
"This sixty-sixth volume of the Annotated Leading Cases of International Criminal Tribunals contains the decision taken by the ECCC on 16 November 2018 in Case 002/02. It provides the reader with the full text of the decision, identical to the original version and including the separate opinion. A istinguished expert in the field of international criminal law has commented on this decision."